PENYULUHAN KESEHATAN DIABETES MELITUS DAN APLIKASI SENAM KAKI PADA LANSIA DI PANTI JOMPO BASILAM - Mei Adelina Harahap; Nanda Suryani Daulay (Universitas Aufa Royhan Di Kota Padangsidipuan, 2020)
Nowadays, modern lifestyle with food menu choices and unhealthy ways of life are increasingly spreading to all levels of society, causing an increase in the number of degenerative diseases, namely diseases that are not contagious but can be inherited. One of the degenerative diseases that require proper and serious treatment is diabetes mellitus (DM). According to reports from several places in Indonesia, the incidence and complications of DM is quite scattered so that it can be said to be one of the national problems that should receive more attention. The purpose of this service is to increase knowledge and awareness of the elderly about diabetes mellitus and the application of foot exercises to the elderly. The form of activity carried out was counseling on Diabetes Mellitus Foot Gymnastics for the Elderly at the Basilam Nursing Home. The counseling activity which was carried out went well by the elderly, the activity seemed enthusiastic in participating in the counseling activity about Diabetes Mellitus and the application of foot exercises for the elderly at Basilam Elderly Beach. This is evidenced by the enthusiasm of the elderly who carry out activities regularly and in an orderly manner as well as listening to counseling about Diabetes Mellitus and the application of Diabetes Mellitus Foot Exercise, sticking banners and photos together by the activity committee and the elderly.